Bit of Quantum - Ye, Valerie Min (Nanyang Technological University, 2020)
In the view of humankind’s unending pursuit of the true meaning of existence, where does the question of ‘where we come from’ fit in? A word play on the unit profile in Quantum and how this installation presents a teensy bit of the vast amount of information documented about Quantum Theory. Bit of Quantum is an audio-visual installation, that serves as a glimpse into the improbable subatomic workings in the core of our sun.